2015
DOI: 10.3906/sag-1406-145
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in ocular and central nervous systems: optical coherence tomography study in normal-tension glaucoma and Alzheimer disease*

Abstract: IntroductionGlaucoma is among the leading causes of blindness worldwide. As an optic neuropathy, glaucoma is characterized by progressive retinal ganglion cell death. Elevated intraocular pressure is the only commutable risk factor for glaucoma. However, despite the effective control of intraocular pressure (IOP), the progression of visual field loss suggests that IOP-independent mechanisms may also play a role in glaucomatous degeneration in patients having normal-tension glaucoma (NTG) (1,2).Based on the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 43 publications
2
37
1
3
Order By: Relevance
“…Possibly, AD is a risk factor for glaucoma, or AD and glaucoma share a pathophysiological process with retinal neurodegeneration as final common pathway. Two recent studies of Eraslan et al and Cesareo et al, measuring RNFL with OCT, visual field defects with frequency doubling technology, and optic nerve head morphology with HRT, showed similar patterns of RNFL thinning, visual field loss, and optic nerve head morphology in AD and normal tension glaucoma [10,44]. Consequently, it seems very challenging to discriminate retinal changes due to AD from retinal changes due to glaucoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Possibly, AD is a risk factor for glaucoma, or AD and glaucoma share a pathophysiological process with retinal neurodegeneration as final common pathway. Two recent studies of Eraslan et al and Cesareo et al, measuring RNFL with OCT, visual field defects with frequency doubling technology, and optic nerve head morphology with HRT, showed similar patterns of RNFL thinning, visual field loss, and optic nerve head morphology in AD and normal tension glaucoma [10,44]. Consequently, it seems very challenging to discriminate retinal changes due to AD from retinal changes due to glaucoma.…”
Section: Discussionmentioning
confidence: 98%
“…With OCT, retinal changes are visualized both in ophthalmological disease and in neurodegenerative disease. Previous studies have shown that the retinal nerve fiber layer (RNFL) thickness and ganglion cell layer (GCL) thickness are reduced in subjects with multiple sclerosis (MS) [5], Parkinson disease (PD) [6], and AD [7–31].…”
Section: Introductionmentioning
confidence: 99%
“…Current OCT research investigating visual system degeneration in various neurological diseases produces compelling evidence for retinal thinning, particularly in MCI and AD (see summary in Table 1 ). While a subset of these studies have shown specific deterioration of the GCL along with the inner plexiform layer (IPL) ( 33 , 37 , 71 , 74 ), the majority have demonstrated thinning of the RNFL, especially in the superior and inferior quadrants, with a focus on the peripapillary region [peripapillary retinal nerve fiber layer (pRNFL)] surrounding the optic disk ( 21 , 34 , 35 , 37 , 50 , 65 , 68 , 71 , 74 , 78 , 83 , 92 , 113 , 114 ). As the inner-most layer of the ocular fundus, this area is composed of RGC axonal projections leading to the optic nerve.…”
Section: Oct Findings In Admentioning
confidence: 99%
“…Although a couple of studies failed to find differences in retinal thickness between patients with AD or MCI and matched HC ( 45 , 92 ), many more studies detected significant RNFL structure abnormalities in AD and MCI patients compared with matched HC ( 32 , 37 , 38 , 41 44 , 46 , 50 , 67 , 71 73 , 75 , 76 , 78 , 79 , 81 , 82 , 87 , 114 116 ). These reports have indicated that RNFL thickness in the patients was substantially decreased in all quadrants or that there were specific reductions in the supraretina and infra-retina.…”
Section: Oct Findings In Admentioning
confidence: 99%
“…Установлено также снижение толщины сетчатки во всех отделах макулярной зоны с максимальным истончением в периферических отделах, относящихся к магноцеллюлярной системе [26]. Подобный паттерн атрофии клеток отмечают при глаукоме [27,28], сходство в патогенезе данных заболеваний подтверждают и другие исследования [29,30]. Результаты оценки толщины СНВС при болезни Паркинсона более разнородны и указывают на преимущественное снижение толщины СНВС в височном секторе [18,20,29], что больше соответствует атрофии зрительного нерва при митохондриальных заболеваниях, таких как наследственная оптическая невропатия Лебера [31].…”
Section: Discussionunclassified